Built Environment Education. Fostering Growth in School Children - Magdalina Polinova Rajeva (Universidad Autónoma de Madrid, 2017)
The focus of this paper is on the importance of communicating architecture to children in Bulgaria in order to increase their attitude towards the built environment and to develop their understanding of different social tendencies which affect it. The aim of this article is by investigating and analyzing different theoretical studies in the field of the Built Environment Education to create a general outline of an architectural course that can be used as a teaching method enabling creative educational growth of children in school in favour of a more just society. The paper introduces the developed methods and concepts concerning Built Environment Education in Bulgaria. Keywords: Children, School, Architecture, Education, Environment.   Educación Ambiental Construida. Fomento del Crecimiento en los Estudiantes El objetivo de este trabajo es comunicar la importancia de la arquitectura a los niños en Bulgaria con el fin de aumentar su actitud hacia el entorno construido y desarrollar su comprensión de las diferentes tendencias sociales que lo afectan. El objetivo de este artículo es investigar y analizar diferentes estudios teóricos en el campo de la Educación Ambiental Construida para crear un esquema general de un curso de arquitectura que pueda ser utilizado como un método de enseñanza que permita un crecimiento educativo creativo de los niños en la escuela para el desarrollo de una sociedad más justa. El documento presenta los métodos y conceptos desarrollados acerca de la Educación Ambiental Construida en Bulgaria. Descriptores: Niños, Escuela, Arquitectura, Educación, Ambiente.   Educação Ambiental Construida. Promovendo o Crescimento em Crianças Escolares O objetivo deste trabalho é comunicar a importância da arquitetura às crianças em Bulgária com o objectivo de as sensibilizar para o ambiente construído e para o desenvolvimento de uma compreensão das suas dinâmicas sociais. O objetivo deste artigo é investigar e analisar diferentes estudos teóricos no campo da Educação Ambiental Construída para criar um curso de arquitetura que pode ser usado como método de ensino e permitir uma educação criativa na Escola e o desenvolvimento de uma sociedade mais justa. O documento apresenta os métodos e conceitos desenvolvidos relacionados com a Educação Ambiental Construída na Bulgária. Palavras-chave: Crianças, Escola, Arquitetura, Educação, Ambiente.